2008
DOI: 10.1152/ajpregu.00691.2007
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of pneumoperitoneum on renal function: involvement of the endothelin and nitric oxide systems

Abstract: The mechanism underlying this phenomenon is largely unknown. This study was designed to investigate the involvement of endothelin (ET)-1 and nitric oxide (NO) systems in IAP-induced renal dysfunction. Rats were subjected to IAP of 14 mmHg for 1 h, followed by a deflation for 60 min (recovery). Four additional groups were pretreated with 1) ABT-627, an ET A antagonist; 2) A-192621, an ETB antagonist; 3) nitroglycerine; and 4) N G -nitro-L-arginine methyl ester, a NO synthase inhibitor, before IAP. Urine flow ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 47 publications
1
27
1
3
Order By: Relevance
“…In Tierversuchen zeigte sich des Weiteren eine Interaktion mit dem Stickstoffmonoxid-(NO-) und Endothelinsystem. Die negativen Effekte konnten durch eine Vorbehandlung der Tiere mit Nitroglyzerin vermindert werden [8]. Auch an der Leber kommt es zu einem verminderten Blutfluss, der sich in einer subklinischen hepatischen Dysfunktion mit um bis zu 100% gestiegenen Transaminasewerten widerspiegelt [9].…”
Section: Splanchnikusgebiet Nieren-und Leberfunktionunclassified
“…In Tierversuchen zeigte sich des Weiteren eine Interaktion mit dem Stickstoffmonoxid-(NO-) und Endothelinsystem. Die negativen Effekte konnten durch eine Vorbehandlung der Tiere mit Nitroglyzerin vermindert werden [8]. Auch an der Leber kommt es zu einem verminderten Blutfluss, der sich in einer subklinischen hepatischen Dysfunktion mit um bis zu 100% gestiegenen Transaminasewerten widerspiegelt [9].…”
Section: Splanchnikusgebiet Nieren-und Leberfunktionunclassified
“…Determination of urinary NGAL and KIM-1: NGAL and KIM-1 were determined from a single 10 µl specimen of urine and were measured with commercially available ELISA kits (NGAL Rapid ELISA Kit; Bio Porto Diagnostics, Gentofte, Denmark) and (Wuhan EIAab Scitween pneumoperitoneum and kidney injury in rat model [5]. Others reported similar results in human [6,7].…”
Section: Samples Collectionmentioning
confidence: 99%
“…This is particularly important in cases of laparoscopic nephrectomy, because maintaining the function of the remnant kidney is critical. Increased intra-abdominal pressure associated with pneumoperitoneum leads to compression of the kidney parenchyma, reduced cardiac output and systemic hormonal effects, which result in decreased Glomerular Filtration Rate (GFR) and urinary output [1][2][3][4][5]. In a review of five animal studies, Shafer, et al demonstrated a decrease in renal perfusion ranged from 12% to 14% [14].…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…The rats were prepared for clearance studies, as described earlier [30,31]. After a 60-min equilibration period, two baseline clearance periods of 30 min each were obtained (IAP = 0).…”
Section: Clearance Studiesmentioning
confidence: 99%
“…However, the involvement of the NO system in the adverse effects of pneumoperitoneum on renal perfusion and function has not yet been explored. For this purpose, we recently investigated the involvement of NO in pneumoperitoneum-induced renal dysfunction in rats [30,31].…”
mentioning
confidence: 99%